2008
DOI: 10.1111/j.1399-5448.2007.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Very high and increasing incidence of type 1 diabetes mellitus in Newfoundland and Labrador, Canada

Abstract: The province of NL has one of the highest incidences of T1DM reported worldwide. The incidence is increasing over the 19-yr study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
2
19
2
Order By: Relevance
“…We found the lowest incidence in the subgroup 0 to 4 years, and the highest in children aged between 10 and 14 years. The differences between the age groups were mentioned by many other authors (7,8,11), but some of them found the highest incidence in children aged 5-9 years.…”
Section: Discussionmentioning
confidence: 87%
“…We found the lowest incidence in the subgroup 0 to 4 years, and the highest in children aged between 10 and 14 years. The differences between the age groups were mentioned by many other authors (7,8,11), but some of them found the highest incidence in children aged 5-9 years.…”
Section: Discussionmentioning
confidence: 87%
“…T1DM accounts for about 5-10 % of all cases of diabetes, and its incidence seems to be increasing worldwide [18][19][20][21]. It results from an autoimmune destruction of insulin-producing beta cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the oral glucose tolerance test, a person's blood glucose level is measured after a fast and 2 h after drinking a glucose-rich beverage. If the 2-h blood glucose level is between 140 and 199 mg/dl, the person tested has pre-diabetes, and if the 2-h blood glucose level is at 200 mg/dl or higher, the person has diabetes [4].…”
Section: Diagnosis and Management Of Type I Diabetes In Children And mentioning
confidence: 99%
“…In the United States, the reported incidence is 19 per 100,000 children [3]. Parts of Canada, such as Newfoundland, have a higher incidence, at 35 per 100,000 per year, than the United States [4], whereas the incidence in Quebec is lower, at 15 per 100,000 per year in children younger than 15 years of age [5]. Data from the Centers for Disease Control and Prevention show that more than 13,000 children and adolescents are diagnosed with type I disease each year, with a resulting prevalence of 1.7 per 1000 [6].…”
Section: Incidence and Pathophysiology Of Type I Diabetes In Childrenmentioning
confidence: 99%